Unveiling Algorithmic Biases Through Personas: A Comparative Analysis of ENEM’s Essays on Gemini - Mendes, Luana B.; Guimarães, Keslley W. C.; Valenciano, Igor C.; Silva, Bianca Cristina O. do E. S.; Souza, Patricia de; Ventura, Thiago M.; Oliveira, Allan G. de (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2025.13714, 2025)
The advancement of generative Artificial Intelligence (AI) models raises questions about their objectivity in evaluation tasks. This study investigates whether AI can assess essays in Portuguese impartially and how assigning author personas affects their evaluations. Using a comparative methodology, 801 essays were evaluated by a human and by the Gemini AI using anonymously and with five different personas. The AI demonstrated bias, assigning higher scores to personas perceived as more experienced and lower scores to less experienced ones. The research concludes that AI systems can amplify demographic biases, highlighting the risks of their application in educational contexts and the need to develop audit mechanisms to ensure equity.